In Brief. (Chronicle of Higher Education, 1981)
The article offers news briefs related to education in the U.S. A law firm in Redmund, Washington has advertised in students newspapers that encouraged those willing women to be surrogate mothers. Central Connecticut State College has canceled classes for two days due to electrical problem. Alan Rosenblum and Bruce Malarino, computer specialists at the New York Institute of Technology has been alleged for using the computer of the institute to run a private business.